IMMUNOGLOBULINS IN COLOSTRUM OF SOWS WITH PORCINE REPRODUCTIVE AND RESPIRATORY SYNDROME - PRRS - Michal ROLINEC (Journal of Central European Agriculture, 2012)
The aim of this study was to examine the effect of PRRS occurrence on sow colostrum immunological quality. We realised the experiment on 20 sows (breed: Large white). From farm without presences of PRRS were 10 sows and other 10 sows were from farm with presence of PRRS. We took the samples of sows colostrums during sucking. We detected concentration of immunoglobulins (IgG, IgA, IgM) in sows colostrum in time of 0 hours to 12 hours after beginning of farrowing with pig Ig ELISA quantitation kits. We determined statistically significant (P<0.01) higher concentration of IgG at the beginning of farrowing, 3 hours, 6 hours and 12 hours from beginning of farrowing in favour of farm without presence of PRRS. We determined statistically significant (P<0.01) higher concentration of IgA at 6 and 12 hours from beginning of farrowing in favour of farm without presence of PRRS. We determined statistically significant (P<0.01) higher concentration of IgM at 6 and 12 hours from beginning of farrowing in favour of farm without presence of PRRS. Lower concentrations of colostral immunoglobulins in group with PRRS can be caused of presence of PRRS. Virus PRRS can evocate synthesis of cytokine IL-10, which inhibited the function of macrophages and lymphocytes and so PRRS decrease the production of immunoglobulins and their concentration in blood of sows and consequently also concentration of immunoglobulins in sows colostrum.